KARAKTERISTIK TERMAL CAMPURAN BIOSOLAR DAN BIODIESEL MINYAK BIJI RANDU (CEIBA PENTANDRA) - Nofal Kharis Kharis; Hary Sutjahjono Sutjahjono; Digdo Listyadi Setyawan; Nasrul Ilminnafik Ilminnafik (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
Research involving thermal characteristics of mixture of biodiesel from kapok (ceibapentandra) and biosolar has been conducted. Biosolar and biodiesel mixed with 5 different composition:B0 (100% biodiesel), B10 (10% biodiesel), B20, B30, and B100 (100% biodiesel). Laboratory experimentwas conducted to obtain several fuel characteristics: heating value, flash point, density, and viscosity.Biosolar is evaporated at a temperature of 120°C and then the steam is flowed to a bunsen burner with afixed discharge (2 ml/minute) and mixed with air in the equivalent ratio variation (φ) 0.8; 1; and 1,2 andturned on. The resulting flame was recorded with the camera and an analysis of the flame was carriedout. Thermal characteristics of this biodiesel have properties in accordance with biosolar standards ofPT Pertamina Indonesia. The heating value of biosolar is 10,602 cal/gram and biodiesel is 8,641cal/gram, and the mixture has heating value among them. As for the characteristics of the flame with highheat values, the core of the flame is covered in blue which shows the highest heat value.